Implementasi Kebijakan Transformasi Perpustakaan Berbasis Inklusi Sosial Dalam Upaya Peningkatan Indeks Pembangunan Literasi Masyarakat (IPLM): Studi Pada Dinas Kearsipan dan Perpustakaan Provinsi Nusa Tenggara Timur - Oktavianus Nuwa; William Djani; David Wilfrid Rihi; Delila Anggelina Nahak Seran (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research aims to analyze and explain the implementation of the social inclusion-based library transformation policy at Provinsi Nusa Tenggara Timur Archives and Libraries Office. This research uses a qualitative method with a case study research type and data collection procedures using in-depth interviews. The research findings show that the implementation of the Social Inclusion-Based Library Transformation (SIBLT) policy at the Office of Archives and Libraries of Provinsi Nusa Tenggara Timur has not been carried out massively. This is due to various factors, such as limited resources, including budget, time, human resources, and facilities and infrastructure; miscommunication between related organizations that have the authority to implement SIBLT; poor characteristics of the implementing agency, limited competence and number of staff, inconsistent level of hierarchical control, and poor formal and informal relationships between agencies; economic, social, and political factors, where economic resources are limited, community involvement is quite low, and support from the provincial government is inconsistent; implementing disposition issues, where SIBLT policy implementing actors do not have sufficient understanding of the program in question, and program implementing staff do not have sufficient intensity in implementing the SIBLT program.